MEMBACA LUKAS 12:10 DAN MAKNA TEOLOGI MENGHUJAT ROH KUDUS (READING LUKE 12:10 AND THE THEOLOGY MEANING OF BLASPHEMES AGAINST THE HOLY SPIRIT) - Sri Wahyuni; Susanti Embong Bulan (QUAERENS: Journal of Theology and Christianity Studies, 2020)
The word blaspheming the Holy Spirit as stated in Luke 12:10 raises many different opinions and interpretations. Blaspheming the Holy Spirit is revealed as an unforgivable sin which is a problem that needs to be well understood so that God's people can be avoided from such sin. For this reason, through this study it is hoped to get the meaning as it should so that such sins can be avoided. The results of the study concluded that blaspheming the Holy Spirit means that an attitude that opposes the work of the Holy Spirit and consciously and deliberately and continually rejects the work of the Holy Spirit that enables humans to become like Christ. Kata menghujat Roh Kudus sebagaimana yang dinyatakan dalam Lukas 12:10 menimbulkan banyak pendapat dan tafsiran yang berbeda. Menghujat Roh Kudus dinyatakan sebagai dosa yang tidak dapat diampuni menjadi persoalan yang perlu dipahami dengan baik sehingga umat Tuhan dapat terhindari dari dosa demikian. Untuk itu melalui kajian ini diharapkan mendapatkan makna sebagaimana mestinya sehingga dosa yang demikian dapat dihindari. Hasil kajian menyimpulkan bahwa menghujat Roh Kudus memiliki makna bahwa suatu sikap yang melawan pekerjaan Roh Kudus dan penolakkan dengan sadar dan sengaja serta terus-menerus terhadap karya Roh Kudus yang memampukan manusia menjadi serupa dengan Kristus.